HXE 420 - Literature In The Renaissance Period January 2016 - PPIK, Pusat Pengajian Ilmu Kemanusiaan (Universiti Sains Malaysia, 2016)
Please check that this examination paper consists of TWO printed pages before you begin the examination. Answer any FOUR questions.